Evaluation of Information Technology Governance Using COBIT 5 and ISO/IEC 38500 - Tubagus Toifur; Kusrini Kusrini; Agung Budi (JOIN (Jurnal Online Informatika), 2022)
Infrastructure Section, Information and Communication Technology Development Division, South Tangerang City Communication and Information Office, one of the main tasks and functions is to provide services and management of internet network infrastructure for all Regional Apparatus Organizations (OPD) in South Tangerang City. The implementation of the Infrastructure Section is constrained by the problem of employee competence that has not reached the standard in internet network management and service, from these problems the researcher intends to evaluate governance using the COBIT 5 framework and ISO/IEC 38500 with recommendations for improvement in the Infrastructure Section. This study uses PAM (Process Assessment Model) with the Guttman scale to determine the results and level of capability. The use of COBIT 5 in this research will focus on the domain of EDM (Evaluate Direct Monitor) point 04, Ensure Resource Management and MEA (Monitor, Evaluate and Assessment) point 01, Performance and Conformance. The results and the level of capability obtained during the research were level 2 Managed Process with a value of 2.46 with a gap of 0.54. The level expected by the Infrastructure Section is at level 3 Established Process with a value of 3.00. Recommendations for achieving Level 3 are used ISO/IEC 38500.